Uncovering hidden collections - Otazua, R; Truman, S; Egerton, F (Bodleian Libraries, University of Oxford, 2022)
On our poster we would like to showcase the work that we have done in the Latin American Centre library to catalogue more than 200 boxes of grey literature and printed ephemera on various Latin American countries. This collection is unique to the Bodleian Libraries and has proven very useful to researchers and students of Latin American topics. We will focus on the outcomes of this project, which resulted in thousands of new items being visible to the academic community.